Phosphorylation of Glutamine Synthetase on Threonine 301 Contributes to Its Inactivation During Epilepsy - Huyghe, Deborah; Denninger, Andrew R.; Voss, Caroline M.; Frank, Pernille; Gao, Ning; Brandon, Nicholas; Waagepetersen, Helle S.; Ferguson, Andrew D.; Pangalos, Menelas; Doig, Peter; Moss, Stephen J. (Frontiers in Molecular Neuroscience, 2019)
The astrocyte-specific enzyme glutamine synthetase (GS), which catalyzes the amidation to glutamate to glutamine, plays an essential role in supporting neurotransmission and in limiting NH4+ toxicity. Accordingly, deficits in GS activity contribute to epilepsy and neurodegeneration. Despite its central role in brain physiology, the mechanisms that regulate GS activity are poorly defined. Here we demonstrate that GS is directly phosphorylated on threonine residue 301 (T301) within the enzyme active site by cAMP-dependent protein kinase. Phosphorylation of T301 leads to a dramatic decrease in glutamine synthesis. Enhanced T301 phosphorylation was evident in a mouse model of epilepsy, which may contribute to decreased GS activity seen during this trauma. Thus, our results highlight a novel molecular mechanism that determines GS activity under both normal and pathological conditions.